CREB controls cortical circuit plasticity and functional recovery after stroke - L. Caracciolo (Nature Portfolio, 2018)
Increasing excitability in the peri-infarct area enhances motor recovery after stroke. Here the authors show that expressing CREB, a transcription factor known for its role in synaptic plasticity, or increasing activity of CREB-expressing cells near the stroke site improves recovery in an effect that is strong enough that it can be used to turn on and off motor recovery after stroke.